Latin America : new challenges to growth and stability - Iakova, Dora; International Monetary Fund ([Washington, District of Columbia] : International Monetary Fund, 2014)
Over the past fifteen years countries in Latin America made tremendous progress in strengthening their economies and improving living standards. Although output fell temporarily during the global financial crisis, most economies staged a rapid recovery. However, economic activity across the region has been cooling off and the region is facing a more challenging period ahead. This book argues that Latin America can rise to the challenge, and policymakers in the region are already implementing reforms in education, energy, and other sectors. More is needed, and more is possible, in Latin America's quest to continue to improve living standards.
Latin America: rising to new challenges / Dora Iakova, Sebastian Sosa, and Alejandro Werner -- Potential growth in Latin America / Sebastian Sosa, Evridiki Tsounta, and Hye Sun Kim -- After the boom: commodity prices and economic growth in Latin America and the Caribbean / Bertrand Gruss -- Commodity price cycles: the perils of mismanaging the boom / Gustavo Adler and Sebastian Sosa -- Terms-of-trade booms: saving-investment patterns and a new metric of income windfall / Gustavo Adler and Nicolas E. Magud -- External conditions and debt sustainability in Latin America / Gustavo Adler and Sebastian Sosa -- Has fiscal policy become less procyclical in Latin America? / Alexander Klemm -- Riding global waves: the impact of external financial shocks on emerging market economies / Gustavo Adler and Camilo E. Tovar -- Global financial shocks and gross capital flows in Latin America / Gustavo Adler, Marie L. Djigbenou, and Sebastian Sosa -- Spillovers to Latin America from the normalization of U.S. monetary policy / Alexander Klemm, Andre Meier, and Sebastian Sosa -- Housing markets in Latin America: do we need to worry about a bubble? / Luis Cubeddu, Camilo E. Tovar, and Evridiki Tsounta.
Editors: Dora Iakova, Luis M. Cubeddu, Gistabo Adler, and Sebastian Sosa.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Economic development -- Latin America; Fiscal policy -- Latin America; Prices -- Latin America; Capital movements -- Latin America; Financial risk management -- Latin America; Latin America -- Economic conditions; Latin America -- Economic policy; Electronic books